Evolution of ungulate mating systems: Integrating social and environmental factors. Issue 11 (15th April 2020) - Bowyer, R. Terry; McCullough, Dale R.; Rachlow, Janet L.; Ciuti, Simone; Whiting, Jericho C.
Abstract: Ungulates exhibit diverse mating systems that range from monogamous pair territories to highly polygynous leks. We review mating systems and behaviors across ungulates and offer a new approach synthesizing how interacting factors may shape those mating systems. Variability exists in mating systems among and within species of ungulates and likely is affected by predation risk, availability of resources (food and mates), habitat structure, and sociality. Ungulate mating systems may be labile as a consequence of the varying strength of those interacting factors. In addition, degree of polygyny and sexual dimorphism in size are associated with the evolution of mating systems. Neither male–male combat nor paternal care, however, can completely explain differences in sexual size dimorphism for ungulates, a necessary component in understanding the development of some mating systems. Whatever the evolutionary pathway, sexual segregation limits paternal care allowing more intense male–male competition. Selection of habitat structure, because it modifies risk of predation, is a major determinant of sociality for ungulates. Likewise, ruggedness and steepness of terrain limit the types of mating systems that can occur because of limitations in group size and cohesiveness, as well as the ability of males to herd even small groups of females effectively. The quality and defensibility of resources affect mating systems, as does the defensibility of females. Population density of females also may be a critical determinant of the types of mating systems that develop. Size of groups likewise constrains the types of mating tactics that males can employ. Our aim was to use those relationships to create a broad conceptual model that predicts how various environmental and social factors interact to structure mating systems in ungulates. This model provides a useful framework for future tests of the roles of both ecological and social conditions in influencing the social systems of ungulates. Abstract : We provide a new approach to understanding mating systems in ungulates. We integrate both social and environmental factors in doing so. We develop a predictive model to help understand the evolution of these unique behaviors, which should help to direct future studies.